2017
DOI: 10.1088/1367-2630/aa7bde
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive elimination of synchronization in coupled oscillator

Abstract: We present here an adaptive control scheme with a feedback delay to achieve elimination of synchronization in a large population of coupled and synchronized oscillators. We validate the feasibility of this scheme not only in the coupled Kuramoto's oscillators with a unimodal or bimodal distribution of natural frequency, but also in two representative models of neuronal networks, namely, the FitzHugh-Nagumo spiking oscillators and the Hindmarsh-Rose bursting oscillators. More significantly, we analytically illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…(33b) and (34b) and E death obtained numerically using Eqs. (22) and (29). The general tendency is well captured by Eqs.…”
Section: Optimal Feedback Parametersmentioning
confidence: 67%
See 2 more Smart Citations
“…(33b) and (34b) and E death obtained numerically using Eqs. (22) and (29). The general tendency is well captured by Eqs.…”
Section: Optimal Feedback Parametersmentioning
confidence: 67%
“…Global feedback may also desynchronize oscillator assemblies. Several types of mean-field feedback that efficiently desynchronize oscillators have been proposed [21][22][23][24][25][26][27][28][29]. Moreover, other behaviors may be realized through global feedback.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where c 1,2 with c 1 + c 2 = 2 are the widths of the two peaks in h and 2d > 0 is the distance between the two peaks. This distribution is symmetric with zero mean [65] for c 1,2 = 1. Following the analysis with the unimodal distribution, we obtain [ASC] as…”
Section: Synchronization Stability Condition Analytics: From Dismentioning
confidence: 94%
“…On the contrary, Parkinson's disease and epilepsy are often related to an adverse effect of synchrony in large neuronal populations [7][8][9][10][11] . Numerous model studies suggested various techniques for the control of synchrony to cope with this adverse effect [12][13][14][15][16][17][18][19][20][21][22][23][24] . These studies exploited models of (infinitely) many or several 25 mean-field coupled limit-cycle oscillators and assumed that the control input affects the whole population or at least its significant part(s).…”
Section: Introductionmentioning
confidence: 99%